Translanguaging with Multisensory Storytelling: A Conceptual Framework for Enhancing First-Grade Language Acquisition in Multilingual Contexts - Tarjadinata, Veronica (Journal of English Education Forum (JEEF), 2025)
Language acquisition during early childhood lays the foundation for literacy, cognitive development, and social integration. In multilingual educational contexts, such as Indonesia, children often encounter challenges when learning Bahasa Indonesia while English dominates instructional practices in international schools. Traditional monolingual and grammar-based approaches may lead to disengagement and limited vocabulary retention among early learners. This literature review synthesizes research on two complementary pedagogical strategies: translanguaging and multisensory storytelling. Translanguaging, a pedagogical practice that draws upon learners’ full linguistic repertoires, fosters cognitive flexibility, identity affirmation, and metalinguistic awareness. Multisensory storytelling, rooted in multimodal learning theory, integrates visual, auditory, tactile, and kinesthetic stimuli to enhance comprehension, memory, and emotional engagement. A systematic review of 42 peer-reviewed studies published between 2000 and 2024 was conducted using databases such as Scopus, ERIC, and Web of Science. Thematic analysis revealed four critical domains: (1) translanguaging as a scaffold for linguistic and cultural inclusion; (2) multisensory storytelling for vocabulary retention and emotional engagement; (3) conceptual intersections between the two methods; and (4) implementation barriers, including policy constraints and teacher preparedness. Findings indicate that the integration of translanguaging with multisensory storytelling can transform language learning into an interactive, inclusive, and culturally responsive experience. However, gaps remain regarding empirical validation, scalability, and long-term outcomes. This review concludes with recommendations for teacher education, curriculum design, and future research to operationalize this integrated approach in multilingual classrooms.